2021
DOI: 10.1080/00071005.2021.1960267
|View full text |Cite
|
Sign up to set email alerts
|

Defending Aesthetic Education

Abstract: In this paper, I offer a defence of aesthetic education in terms of aesthetic experience, claiming that aesthetic experience and art appreciation is a vital component of a flourishing life. Given schools have an important role to play in helping prepare young people for their adult lives, it is crucial they should consider how best to equip students with the means to achieve a flourishing life. It is on these grounds I defend arts education as compulsory across the curriculum. In order to adopt this position, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…I do not hold that such ‘aesthetic emotions’ are uniquely tied to art, but instead follow Dewey (1934) in claiming that feelings and emotions of wonder, the sublime, awe, joy, etc., may be felt in relation to artworks, nature and are an extension of human experience 1 . On my account, aesthetic experiences contain both emotional and cognitive components (D'Olimpio, 2021, p. 2). Yet I do argue that such aesthetic experiences are more likely to be made present to people in subtle and dynamic ways if they are taught it is an option, particularly afforded by artworks, and if they are educated in an open, receptive attitude that affords them the understanding that art may be experienced in such a manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I do not hold that such ‘aesthetic emotions’ are uniquely tied to art, but instead follow Dewey (1934) in claiming that feelings and emotions of wonder, the sublime, awe, joy, etc., may be felt in relation to artworks, nature and are an extension of human experience 1 . On my account, aesthetic experiences contain both emotional and cognitive components (D'Olimpio, 2021, p. 2). Yet I do argue that such aesthetic experiences are more likely to be made present to people in subtle and dynamic ways if they are taught it is an option, particularly afforded by artworks, and if they are educated in an open, receptive attitude that affords them the understanding that art may be experienced in such a manner.…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere White (2011, p. 24) defends the arts as offering a universal source of enjoyment and personal fulfilment, and Reiss and White (2013, p. 18) justify the inclusion of good literature on the curriculum for its educational qualities as well as affording everyone an intrinsically valuable activity. I engage in more detail with Reiss and White's arguments in D'Olimpio (2021). …”
mentioning
confidence: 96%
“…Along with literature, mathematics, history, and physical training, aesthetic education has become integral to many official curricula all over the world (D’olimpio, 2022 ). The sudden outbreak of the Covid-19 pandemic has shown that the educational sector is in high need of the development of innovative technologies and methodological approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Today there is a need to expand what is meant by aesthetics and deepen the discussion about the role of aesthetic education in university curricula (Costa et al, 2021 ). Aesthetic experience and the ability to appreciate art are vital personality traits as they allow a person to express themselves and improve morally (D’olimpio, 2022 ). It is believed that aesthetic development generates a sense of autonomy and can also contribute to the creation of an alternative existential meaning, the development of critical thinking, and a focus on feelings (Lutfi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bir zihinsel etkinlik süreci olarak görülen sanat eğitimi çağcıl, özgün, dinamik düşünceler üreten ve yayan sanat eğitimcileri yetiştirmektedir (Kahraman, 2007). Sanat eğitiminin bireyde estetik ve algısal duyarlılıkları geliştirmesinin yanında öğrenme yetisinin gelişimi, eleştirel bakış açısının gelişimi hem bireysel hem de toplumsal iletişiminin gelişimi ve görsel sanatları anlama gibi yararları da bulunmaktadır (D'Olimpio, 2022).…”
Section: Introductionunclassified